Língua e identidade: o crioulo cabo-verdiano em foco - Lopes, Elber Amado Almeida (2024)
This article explores the connection between language and identity in Cape Verde, focusing on the coexistence of Cape Verdean Creole (Kriolu) and Portuguese. These languages reflect the country's history, culture, and social dynamics, shaped by Portuguese colonization, which established Portuguese as the official language while Cape Verdean Creole remained the mother tongue. The main goal is to understand how Cape Verdean Creole contributes to building national identity, emphasizing its cultural and historical importance. Key authors include Maurizzio Gnerre (2009), Stuart Hall (2006), Lélia Gonzalez (1984), Mário Lúcio Sousa (2021), and Manuel Veiga (2009a, 2009b), whose works illuminate the dynamics of power and resistance between these languages. The research adopts a qualitative approach, including a review of existing studies and critical analysis. The study highlights Cape Verdean Creole as a symbol of resistance and belonging, contrasting with the dominance of Portuguese in formal contexts such as education. Despite progress, including the creation of ALUPEC and growing political support, Cape Verdean Creole still faces challenges to being recognized as an official language. The research concludes that its officialization would not only promote social inclusion but also strengthen Cape Verde’s cultural identity. This study encourages further reflection on the value of linguistic diversity and the importance of policies that support mother tongues.